Communicative nature of information society and the main trends of its social and cultural transformation - Shormanbayeva, D.G.; Alzhanova, G.B.; Ivleva, E.N.; Ceydinova, М.А. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the work we consider the communicative nature of the information society and its influence on the process of sociocultural transformation. The task was to prove the influence of the communicative nature of the information society on the process of sociocultural transformation of the system of personal values. The communicative nature of the information society has a whole range of features — the network principle of function-monitoring and distribution, a virtual character, a short-term, spontaneous, «clip» form of presenting information. Informational and communicative processes are being transformed into an alternative informational and communicative environment, which has an ontological status. Social space is decentralized in the context of its virtualization, social institutions are transformed into hyperspace, and a virtual society is being formed. At present, there is a contradiction in the understanding of the system of values that determines social reality. The transformation of values accommodates both traditional ideas about norms and values, as well as axiological innovations that characterize the current process of reassessing values. Multidimensionality and contradictory interpretations of values, their essential content are characteristic for all generations and ages that form a specific socio-cultural state of society, expressed in the appearance of conflicting normative-value paradigms. This process complicates the adaptive potential of individual, it has a deforming effect on personal development; it turns into an increase in maladaptive potential and identity crisis. Modern man demonstrates the dialectical denial of the previously adopted system of norms and values, creates a new hierarchy of higher values of being and society as a whole. In the era of the information society, a person develops towards the individualization of his own being while reducing communication with the social world, which helps to reduce the role of social adaptation of an individual.
Ақпараттық қоғамның коммуникативтік табиғаты жəне оның əлеуметтік-мəдени өзгеруінің негізгі заңдылықтары
Коммуникативная природа информационного общества и основные тенденции его социокультурной трансформации
Keywords: values transformation; information society; virtual society; identity crisis; informational space; timeless conflict; conflict of normative value paradigms